Direct esterification of cinnamic acids with phenols and imidoalcohols: a simple, heteropolyacid-catalyzed procedure - Ruiz, Diego Manuel (2008)
A convenient procedure for the direct esterification of cinnamic acids with phenols or 2-(N-phthalimido) ethanol is described. The method is simple and clean, environmentally friendly and high-yielding for both electron-releasing and electron-withdrawing substituted phenols. The heteropolyacid H 6P2W18O62·24 H2O was employed as catalyst, both bulk and supported on silica. No stoichiometric activation of the carboxyl group or condensing reagents is necessary. The effects of temperature, reaction time, amount of the catalyst used and mole ratio of the reactants on the ester yield were checked. Suitable conditions for the reaction include a 1:1 molar ratio of reactants and a 1 mmol % mass ratio of catalyst to reactant. Eighteen aryl and phthalimidoethyl cinnamates were obtained, yields ranged in 84-95% for most of the esters. The catalyst shown to be reusable for at least three times without occurring an appreciable loss of its activity.